1990
DOI: 10.1177/0305735690182004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tempo and Situational Arousal on the Listener's Perceptual and Affective Responses to Music

Abstract: Based on previous research, this study formulates hypotheses concerning (1) the psychophysical relationship between musical tempo and perceived activity, (2) a nonmonotonic hedonic effect of musical tempo on affective responses, and (3) a shift in this preference function due to differences in situational arousal. An experiment manipulates tempo in the same piece ot music at 14 different speeds varying by equal percentage increases. T he findings appear to support (1) a strong psychophysical relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
2
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 22 publications
9
94
2
4
Order By: Relevance
“…Research focusing on ideal-point judgments has been underrepresented in this literature. Indeed most of the studies exploring ideal-point judgments outside of traditional attitude research have centered on less socially relevant stimuli (Holbrook & Anand, 1990;Riskey, Parducci, & Beauchamp, 1979), with only a few studies relating to social groups or socially relevant judgments (Pettibone, 2000;Pettibone & Wedell, in press;Wedell & Pettibone, 1999;Wedell, Santoyo, & Pettibone, 2005). The current studies continue this latter line of research.…”
Section: Two Types Of Judgmentmentioning
confidence: 71%
“…Research focusing on ideal-point judgments has been underrepresented in this literature. Indeed most of the studies exploring ideal-point judgments outside of traditional attitude research have centered on less socially relevant stimuli (Holbrook & Anand, 1990;Riskey, Parducci, & Beauchamp, 1979), with only a few studies relating to social groups or socially relevant judgments (Pettibone, 2000;Pettibone & Wedell, in press;Wedell & Pettibone, 1999;Wedell, Santoyo, & Pettibone, 2005). The current studies continue this latter line of research.…”
Section: Two Types Of Judgmentmentioning
confidence: 71%
“…The effects of contextual clips were assessed with these target clips. Prior research has shown that tempo judgments follow an ordinal relationship with tempo but that pleasantness judgments follow a single peaked relationship, with an intermediate tempo being rated most pleasant (Holbrook & Anand, 1990;Quin & Watt, 2006). Accordingly, we predicted that participants would show contrast effects on tempo judgments, with target tempos being judged faster in the slow tempo context than in the fast tempo context.…”
Section: Overview Of Experimentsmentioning
confidence: 89%
“…Finally, if pleasantness shifts are related to more general shifts in levels of arousal induced by fast or slow context tempos, then effects might be expected to generalize to all targets. It should be noted that Holbrook and Anand (1990) proposed this type of generalized arousal mechanism and found some support for it in that shifts in preferred tempo reflected changes in arousal state induced by performing different cognitive tasks prior to listening. Because researchers have demonstrated that listening to fast-paced music leads to increases in arousal indicators such as heart rate and performance in stationary cycling and running (Edworthy & Waring, 2006;Waterhouse, Hudson, & Edwards, 2010), the idea of a generalized arousal effect driving ideal point shifts seems plausible.…”
Section: Methodsmentioning
confidence: 97%
“…Music styles and tempos deeply influence consumers in increasing sales of the retail outlets. Pleasant music is associated with longer consumption time (Holbrook & Anand, 1990). The variety of the background music significantly impacts on the consumer perceptions and preferences (Bruner, 1990).…”
Section: Musicmentioning
confidence: 99%